1995
DOI: 10.1159/000120929
|View full text |Cite
|
Sign up to set email alerts
|

Value of Dynamometry in Assessing Upper Extremity Function in Children with Myelomeningocele

Abstract: Children with myelodysplasia frequently have abnormal hand function. Etiologies include brainstem and cervical cord compression due to the Chiari II malformation, syringomyelia, hydrocephalus, and cerebral dysmorphism. Determination of potentially correctable causes of hand dysfunction may be difficult. We describe the use of the Jaymar dynamometer for assessing grip strength as a means of detecting early changes in hand function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…These include cortical, brainstem, cerebellar, and corpus callosum dysmorphologies; seizures; active hydrocephalus; shunt history, including revisions and infections; lowered intelligence; visual impairments; lack of experience-dependent motor and visuo-motor development; primary spinal cord malformations causing weakness, spasticity, or incoordination of the upper limbs; level of spinal cord lesion; lack of trunk control; and scoliosis [2, 11, 12, 15, 17, 20, 22, 23, 25, 27–30, 32, 33, 37, 39]. …”
Section: Introductionmentioning
confidence: 99%
“…These include cortical, brainstem, cerebellar, and corpus callosum dysmorphologies; seizures; active hydrocephalus; shunt history, including revisions and infections; lowered intelligence; visual impairments; lack of experience-dependent motor and visuo-motor development; primary spinal cord malformations causing weakness, spasticity, or incoordination of the upper limbs; level of spinal cord lesion; lack of trunk control; and scoliosis [2, 11, 12, 15, 17, 20, 22, 23, 25, 27–30, 32, 33, 37, 39]. …”
Section: Introductionmentioning
confidence: 99%
“…Regarding mobility, it is possible that hand function and cognitive function are important, especially in children who cannot walk. From the literature it is well known that many children with MMC have poor hand function, reported as weak hands (8,11) and impaired hand coordination (8,12). Cognitive dysfunction in these children has been reported as average to low-average intelligence (9,13,14), as well as impaired visuospatial function (9,13,15) and impaired executive function (9,16).…”
mentioning
confidence: 99%
“…In 1995, Aronin and Kerrick [21] suggested that an acute decrease in upper extremity strength might provide an early indication of an acute neurological complication in children with MM. This could provide a useful way to diagnose neurological complications early before they cause significant morbidity or mortality.…”
Section: Discussionmentioning
confidence: 99%
“…In this journal, Aronin and Kerrick [21] suggested that an uncharacteristic acute decrease in upper extremity strength might provide an early indication of a neurological complication in children with meningomyelocele. They found that children with symptomatic Chiari II malformation, syringomyelia, and worsening hydrocephalus had deterioration of grip and pinch strength.…”
Section: Introductionmentioning
confidence: 99%